Oleaceae plants: a source of metabolites with atheroprotective potential - Filipek, Agnieszka; Czepielewska, Edyta (Frontiers in Pharmacology, 2026)
Atherosclerosis is a leading cause of cardiovascular morbidity and mortality, driven by chronic inflammation, oxidative stress, lipid imbalance, and plaque instability. Bioactive metabolites found in plants of the Oleaceae family, particularly olives (Olea europaea L.), have emerged as promising modulators of these processes. This narrative review highlights several key phytochemicals, such as oleacein and oleuropein (secoiridoids), hydroxytyrosol and oleocanthal (phenylethanoids), acteoside and syringin (phenylpropanoids), oleanolic and ursolic acids (triterpenoids), phillygenin (lignans), caffeic and chlorogenic acids (phenolic acids). These metabolites act by activating the Nrf2/HO-1 antioxidant defence pathway, inhibiting NF-κB-driven inflammation, regulating cholesterol transport (ABCA1/ABCG1 and CD36), protecting the endothelium, and stabilising atherosclerotic plaque. Preclinical studies consistently demonstrate strong anti-atherosclerotic activity, while clinical evidence mainly supports the consumption of polyphenol-rich extra virgin olive oil, which has been linked to improved endothelial function, reduced oxidative and inflammatory markers, and a lower risk of cardiovascular disease. However, robust trials of purified compounds and non-olive Oleaceae species are lacking. Oleaceae-derived phytochemicals offer multi-targeted cardioprotective potential, but their translation into clinical applications remains limited.